O problema do mal: uma abordagem histórica e o discurso demonizante iurdiano como resposta ao sofrimento humano. - Leite, Fúlvio Anderson Pereira (2019)
This dissertation aims to analyze the problem of evil in history and the demonizing discourse of Yurdians. The Yurdian discourse is that demons long to take possession of man and, with this, to objectify, disgrace life, cause misery and pain in man. The discourse and rhetoric of Macedo and his pastors is not intended to bring answers, relief to human suffering, but legitimization, expansion in the religious scene and economic gains. The cases in which liberation from the devil is not obtained are explained by the logic of lack of faith, by the absence of a true surrender to the church - the person has not truly freed himself from the clutches of Satan. Demonology is present in everyday life, crossing all levels of discourses and practices with great fluidity. It is widely incorporated in the daily life of its members, workers and pastors. The demonizing discourse marks the speech and experience of each member. Everything that occurs has a regulating force: that which has been healed by the pastor's prayer of faith; that which has not been healed by the faithful's incredulity. Every human suffering has only one explanation, only one origin: the devil. The origin of any kind of evil always comes from demons who manifest themselves through demonic possession. The Universal Church of the Kingdom of God (UCKG), also has as one of its focuses of action to invest in the dispute for territories of the Brazilian religious field, to analyze the concept of religious field of Pierre Bourdieu and to analyze the rhetoric of the UCKG we use the stages of discourse, as were analyzed by the classical rhetoric of Aristotle: invention, dispositio, elocutio, actio and memory, which represent the four phases through which passes the one who composes a discourse or through which it is believed to pass. Our methodology for the research were some books, newspapers and preaching produced by the UCKG.